Evolution of floor defense efficacy and execution in women's volleyball from national u-14 to senior international - Carlos Echeverría; Enrique Ortega; José Manuel Palao (Asociación Española de Ciencias del Deporte, 2019)
The study aimed to determine the technical performance profile of floor defense regarding execution and efficacy from national U-14 to senior international competitions. The sample of the study was composed of a total of 7,818 game phases from 48 matches in the following divisions: under-14, under-16, under-18, 2nd national senior division, 1st national senior division, and international senior division (World Championship). The study's variables were: "age group and level of competition", the technique used in floor defense, the zone where the defense was executed, attack tempo, and floor defense efficacy. The results indicate that the efficacy of the forearm defense and overhead defense increased up to U-18 category and decreased in senior categories. As the age group and level of competition increases, the efficacy of the different techniques of floor defense and zone defense changed. The attack tempo influenced the efficacy of the floor defense. The study provides data may help to establish the technical and tactical floor defense profiles in women's volleyball and to understand how this action changes throughout the developmental stages of the female volleyball players.